Telaah Terhadap Kitab Mawaid Az-Zam’an Ila Zawaid Ibnu Hibban Karya Al-Hafiz Al-Haisami - Misbah, Muhammad (RIWAYAH, 2015)
Abstract This article explores matters related to the book Mawa>rid az{-Z{am’a>n ila> Zawa>id Ibn H{ibba>n.The book is authored by al-H{a>fizz al-H{ais\ami, disciple of al-H{a>fizz{ al-Ira>qi. It is a book of zawa> id (the book that collects the traditions of certain books that are not loaded by a certain other book.). This book contains authentic traditions of S{ah{i>h{  Ibn H{ibba>n that is not contained in the book of S{ah{i>h{ Bukha> ri and Sah{i>h{ Muslim. The method pursued by al-H{ais\ami in compiling this work as same as he applied to his earlier works. Al-Haisami reconstructs the book of essays by scholars Ibn Hibbaan then considered less systematic, and the formulation of return is based on the chapters of fiqh. Although it is seen so simple, the efforts that he has strived to contribute greatly in later generations. Evidently, his work is considered as a book zawa> id that was first written in the historical development of books of hadith. The figure of al-H{ais\ami is the originator of the writing of the book zawa> id tutored by his teacher, al-H{a>fizz{ al-Ira>qi. Despite a lot of criticism that led to him relating to his carelessness in judging  a hadith, the authors consider it natural. Therefore, negligence and deficiency is the true nature of man.